The The Declining Role of Islamic Politics and The Jokowi’s Factors in the 2024 Presidential Election: A Study of Contemporary Political Policies and Dynamics in Indonesia - Mahyudin, M Alfan Alfian (Religion and Policy Journal, 2024)
Research Problem: This abstract discusses the complex challenges faced by Islamic parties in the 2024 presidential election related to Jokowi's role as president. This report focuses on the dynamics of constellation formation between candidates competing in the 2024 presidential election. Research purposes: The main aim of this abstract is to examine the complexity of the problems faced by Islamic parties in the 2024 presidential election. This report aims to explain why Islamic parties cannot unite, but instead try to defeat each other in the election, due to the existence of forces outside of them who are capable of determine political dynamics in a presidential system. Research methods: Methodologically, this abstract refers to a case study of the experience of Islamic parties in contesting the 2024 presidential election in Indonesia. This report uses a qualitative analysis approach to investigate the political dynamics of the 2024 presidential election which also involves the influence of President Jokowi. Results and Discussion: This abstract discusses the challenges faced by political parties in Indonesia, especially Islamic political parties, in the 2024 presidential election which will be held simultaneously with the legislative elections. President Jokowi's influence is important in popularizing political parties that support the presidential candidates he supports, so that it also influences the results of the legislative elections for each Islamic party. Research Implications and Contributions: This abstract provides a comprehensive overview of the challenges faced by Islamic parties, both those that already exist and those that are just emerging in the 2024 elections. This report invites further research and discussion regarding important external (influence of the President in power) and internal aspects of Islamic parties. (institutional power and their consolidation).